On a possibility of realization of SAW resonator with surface modes conversion - DANICKI, E. (Archives of Acoustics, 1990)
It is shown that surface mode conversion can take place in the reflecting grating on some piezoelectric crystals. When one of the modes is piezoelectrically coupled, while the other is not, the resonator performance will not be sensitive to the IDT position in the resonator cavity region.